Artificial tubular connections between cells based on synthetic lipid nanotubes. Issue 33 (10th April 2017) - Kozintsev, Alexander; Sugihara, Kaori
Abstract : Open-ended artificial tubular connections between cells were controllably fabricated using synthetic lipid nanotubes. Abstract : Tunneling nanotubes (TNTs) have become a major topic of interest as a form of intercellular communication due to their recent discovery. However, research on this subject has often suffered from a lack of controllability in the generation of the nanotubular connections. In this work, we demonstrate a simplified approach to selectively create a direct nanotubular connection between eukaryotic cells by manually manipulating self-assembling lipid nanotubes (LNTs) from inverted hexagonal-phase lipid blocks. The technique requires minimal instrumentation for creating the LNT connection between cells compared to conventional approaches. Based on the diffusion of fluorescent lipids from LNTs into cell membranes ( D = 0.032 ± 0.003 μm 2 s −1 ), the probability of observing membrane fusion between LNTs and cell membranes was estimated as 30%. Among these cell–LNT junctions the resulting structure is open-ended roughly 75% of the time, as evidenced from observations of the diffusion of a water-soluble dye between two cells connected with this nanotubular structure.